The Leadership Style Of The Head Of Madrasah Tsanawiyah At The Modern Islamic Boarding School Darul Hikmah Medan - M Khairul Nasri; Candra Wijaya; Yusuf Hadijaya (STAI Miftahul Ula Nganjuk, 2024)
This study analyzes the leadership style of the Head of Madrasah Tsanawiyah at the Modern Islamic Boarding School Darul Hikmah Medan using a qualitative research approach. The findings indicate that the leadership style prioritizes teacher participation in decision-making processes; however, challenges remain regarding consistency and inclusivity. Efforts to enhance teacher motivation are evident through the provision of physical facilities and incentives, although responsiveness to achievements and feedback requires improvement. Communication is facilitated through regular meetings, yet there is a need for improved assertiveness and conflict management. Overall, continuous efforts to refine managerial processes, communication, and decision-making reflect a commitment to advancing the quality of education in this madrasah.